Visible Light‐Driven, Photocatalyst‐Free Arbuzov‐Like Reaction via Arylazo Sulfones. Issue 22 (7th October 2019) - Qiu, Di; Lian, Chang; Mao, Jinshan; Ding, Yi; Liu, Zerong; Wei, Liyan; Fagnoni, Maurizio; Protti, Stefano
Abstract: A visible light‐induced formation of Aryl‐Phosphorous bonds starting from arylazo sulfones and triaryl (or trialkyl)phosphites in the absence of any photoredox catalyst and any additives was developed. This reaction showed a broad substrate scope and afforded (hetero)aryl phosphonates in good yields and in up to the gram scale. Abstract :